A System for Securing the Durabilityn and Effectiveness of the Three Seas Initiative - Lorek, Artur Marcin (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
Abstract The purpose of this article is to evaluate the security system for the durability and effectiveness of the Three Seas Initiative as an informal union of Central European countries. The author diagnoses a set of elements that constitute potential ‘fuses’ for implementing the goals set by 3SI: embedding the Initiative’s priorities within strategic EU programmes, informalization and decentralization of cooperation, and development of mutual business and economic cooperation. The analysis of the security system has been embedded in the context of contemporary challenges faced by Europe. In order to verify the problem of security mechanisms, desk research was carried out, which consisted of a system (political) analysis and elements of strategic analysis. The result of the research work was to determine the mutual interaction and conditioning of the individual pillars of the durability and effectiveness of 3SI. Thus, evidence was carried out for the legitimacy of recognizing the three previously defined aspects as crucial for the effective operation of the Three Seas Initiative.

Celem niniejszego artykułu jest ocena systemu zabezpieczeń dla trwałości i skuteczności Inicjatywy Trójmorza jako nieformalnego bloku państw Europy Środkowej. Autor diagnozuje zbiór elementów stanowiących potencjalne „bezpieczniki” dla realizacji założonych przez 3SI celów: osadzenie priorytetów Inicjatywy w ramach strategicznych programów UE, odformalizowanie i zdecentralizowanie współpracy oraz rozwijanie wzajemnej współpracy biznesowej i gospodarczej. Analiza systemu zabezpieczeń została osadzona w kontekście współczesnych wyzwań, z jakimi mierzy się Europa. Celem weryfikacji problemu mechanizmów zabezpieczenia przeprowadzono analizę danych zastanych, na co składały się analiza systemowa (polityczna) oraz elementy analizy strategicznej. Rezultatem pracy badawczej było określenie wzajemnego oddziaływania na siebie i warunkowania poszczególnych filarów trwałości i skuteczności 3SI, a tym samym przeprowadzono dowodzenie na rzecz zasadności uznania trzech określonych wcześniej aspektów za kluczowe dla efektywnego działania Trójmorza.
System zabezpieczeń trwałości i skuteczności Inicjatywy Trójmorza
Keywords: Three Seas Initiative; durability; effectiveness; Central Europe; European Union; Trójmorze; Inicjatywa Trójmorza; trwałość; skuteczność